Relationship between the physical environment and different domains of physical activity in European adults: a systematic review - Van Holle Veerle; Deforche Benedicte; Van Cauwenberg Jelle; Goubert Liesbet; Maes Lea; Van de Weghe Nico; De Bourdeaudhuij Ilse (BMC, 2012)
Abstract Background In the past decade, various reviews described the relationship between the physical environment and different physical activity (PA) domains. Yet, the majority of the current review evidence relies on North American/Australian studies, while only a small proportion of findings refer to European studies. Given some clear environmental differences across continents, this raises questions about the applicability of those results in European settings. This systematic review aimed at summarizing Europe-specific evidence on the relationship between the physical environment and different PA domains in adults. Methods Seventy eligible papers were identified through systematic searches across six electronic databases. Included papers were observational studies assessing the relationship between several aspects of the physical environment and PA in European adults (18-65y). Summary scores were calculated to express the strength of the relationship between each environmental factor and different PA domains. Results Convincing evidence on positive relationships with several PA domains was found for following environmental factors: walkability, access to shops/services/work and the composite factor environmental quality. Convincing evidence considering urbanization degree showed contradictory results, dependent on the observed PA domain. Transportation PA was more frequently related to the physical environment than recreational PA. Possible evidence for a positive relationship with transportation PA emerged for walking/cycling facilities, while a negative relationship was found for hilliness. Some environmental factors, such as access to recreational facilities, aesthetics, traffic- and crime-related safety were unrelated to different PA domains in Europe. Conclusions Generally, findings from this review of European studies are in accordance with results from North American/Australian reviews and may contribute to a generalization of the relationship between the physical environment and PA. Nevertheless, the lack of associations found regarding access to recreational facilities, aesthetics and different forms of safety are likely to be Europe-specific findings and need to be considered when appropriate interventions are developed. More research assessing domain-specific relationships with several understudied environmental attributes (e.g., residential density) is needed.